Dual Circularly Polarized Patch Antenna with Improved Interport Isolation for S-Band Satellite Communication - Haq Nawaz; Ahmad Umar Niazi; Mansoor Ahmad (International Journal of Antennas and Propagation)
This paper presents a bi-port, single-layered (planar), dual circularly polarized (CP) patch antenna with improved interport isolation for S-band satellite telemetry and telecommand applications. The dual-port, planar antenna is based on a square-shaped radiator with trimmed corner to achieve CP characteristics (RHCP and LHCP) for excitations from respective ports. However, the RF isolation between the two ports is very low due to strong power leakage from transmit (Tx) to transmit (Rx) port. The externally employed tunable self-interference cancellation (SIC) circuit achieves high isolation between orthogonal ports while axial ratio (AR) is ≤3 dB for both right and left handed circular polarization modes. The employed single-tap SIC circuit/loop attains the high interport isolation through signal inversion mechanism. The proposed antenna design achieves ≥72 dB peak interport isolation in addition to ≥30 dB and 15 dB port to port isolation over the isolation or SIC bandwidths of 15 MHz and 90 MHz (−10 dB bandwidth for both ports), respectively. The port to port isolation performance is improved without significant degradation in antenna radiation characteristics. The validation model of the presented planar antenna based on single element characterizes much better measured interport isolation performance compared to those dual CP printed antennas reported earlier as endorsed through detailed comparison